A Large-Scale Group Decision-Making Consensus Model considering the Experts' Adjustment Willingness Based on the Interactive Weights' Determination. (17th November 2022) - Bai, Shizhen; He, Hao; Luo, Dan; Ge, Mengke; Yang, Ruobing; Bi, Xinrui
Abstract : This study proposes a large-scale group decision-making (LSGDM) consensus model considering the experts' adjustment willingness based on the interactive weights' determination, which can be applied to an LSGDM problem through a case of earthquake shelters. The main contributions of our research are of three aspects as follows. First, the determination method of the interactive weight, which obtains the DMs' attitude towards the decision-making results, is presented. The subgroups' weights are calculated, and the unit adjustment cost for each DM is defined. Second, we introduce an objective consensus threshold by the mean and variance of the consensus level for each subgroup. Subsequently, an identification rule is performed to determine the DM to be adjusted with the large difference and the low adjustment cost. And we developed a novel consensus adjustment method that takes the DMs' adjustment willingness into account to retain as much original information as possible. Thirdly, in order to reduce the subjectivity of the preset consensus threshold and the maximum number of iterations, an objective consensus termination condition that combines the current group consensus level and the consensus adjustment rate is put forward. Finally, the proposed model has demonstrated its effectiveness and superiority based on the comparative and sensitive analysis through a practical example.